Primates and birds of sabulungan; Roles of animals in sculptures, shamanic songs and dances, and the belief system of traditional Mentawaians - Tulius, Juniator; Burman-Hall, Linda (UI Scholars Hub, 2022)
Mentawaians sing ritual songs enshrined in archaic texts referring to particular primates and birds, while ritual and traditional dances imitate how gibbons, sea eagles, and other animals live in the natural world. Mentawaians craft sculptures of endemic primates and unique birds. The bilou gibbon ape and various other animals also symbolize specific sacred knowledge within the sabulungan spiritual belief system and traditional cosmology of Mentawai society. Although some do succeed in surviving, many older traditions have faded away. Among the traditions which continue intact, this report aims to examine the roles of primates and birds across the arts and in the Mentawai belief system to reveal the profound depth of connection between humanity and the natural world throughout Mentawai traditional culture.